2020
DOI: 10.1002/ehf2.13053
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term changes in left and right systolic function following ferric carboxymaltose: a substudy of the Myocardial‐IRON trial

Abstract: Aims The mechanisms underlying the beneficial effect of ferric carboxymaltose (FCM) in patients with heart failure (HF) and iron deficiency (ID) have not been completely characterized. The Myocardial-IRON trial was a double-blind, randomized trial that evaluated myocardial iron repletion following FCM vs. placebo in 53 patients with HF and ID. In this post hoc analysis, we evaluated whether treatment with FCM was associated with cardiac magnetic resonance changes in left and right ventricular function (LVEF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
6
20
1
Order By: Relevance
“…iron administration are not fully known. In a recent substudy of the Myocardial‐IRON trial with patients with left ventricular and RV systolic dysfunction, FCM treatment was associated with a significant improvement in LVEF at 30 days and with a significant and early improvement in RV function 12 . These findings are consistent with our results, which confirmed an increase in the number of patients with normal RV contractility in both the HFpEF and HFrEF subgroups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…iron administration are not fully known. In a recent substudy of the Myocardial‐IRON trial with patients with left ventricular and RV systolic dysfunction, FCM treatment was associated with a significant improvement in LVEF at 30 days and with a significant and early improvement in RV function 12 . These findings are consistent with our results, which confirmed an increase in the number of patients with normal RV contractility in both the HFpEF and HFrEF subgroups.…”
Section: Discussionsupporting
confidence: 91%
“…Since then, this treatment option has been included in the routine pharmacopoeia for outpatient treatment of symptomatic patients with HF and reduced left ventricular ejection fraction (LVEF). Additionally, magnetic resonance imaging (MRI) techniques (T2‐weighted scans) have shown that the iron administered is taken up by the myocardium 11 and can improve LVEF 30 days after administration 12 …”
Section: Introductionmentioning
confidence: 99%
“…iron to patients with HFrEF and ID results in repletion of iron in cardiac muscle and improvements in both right and left ventricular ejection fractions. 65,66 Increases in myocardial iron content generally correlated with improvements observed in markers of HF severity (e.g., quality of life and functional capacity). 65 In an in vitro model with human cardiomyocytes, iron repletion quickly corrected the mitochondrial dysfunction and the impaired contractility and relaxation associated with ID.…”
Section: Mechanistic Effects Of Iron Therapy (Beyond Erythropoiesis)mentioning
confidence: 93%
“…Replenishing iron prevents abnormalities of Ca 2+ handling, improves cardiac function and survival in rat models with HF [ 180 ]. In the Myocardial-IRON Trial, it was found that administering FCM intravenously in iron-deficient HF patients resulted in significant improvement in cardiac magnetic resonance sequences, indicating myocardial iron repletion [ 220 ]. This correction of ID was accompanied by improved right and left ventricular ejection fraction on the 7th day already [ 221 ].…”
Section: Deleterious Biological Consequences Of Iron Deficiencymentioning
confidence: 99%